Optimization of the protein concentration process prepared from residual peanut oil-cake - Gayol, Maria Fernanda (2013)
The objective of this study was to find the best process conditions for preparing protein concentrate from residual peanut oil-cake (POC). The study was carried out on POC from industrial peanut oil extraction. Different protein extraction and precipitation conditions were used: water/ flour ratio (10:1, 20:1 and 30:1), pH (8, 9 and 10), NaCl concentration (0 and 0.5 M), extraction time (30, 60 and 120 min), temperature (25, 40 and 60°C), extraction stages (1, 2 and 3), and precipitation pH (4, 4.5 and 5). The extraction and precipitation conditions which showed the highest protein yield were 10:1 water/flour ratio, extraction at pH 9, no NaCl, 2 extraction stages of 30 min at 40°C and precipitation at pH 4.5. Under these conditions, the peanut protein concentrate (PC) contained 86.22% protein, while the initial POC had 38.04% . POC is an alternative source of protein that can be used for human consumption or animal nutrition. Therefore, it adds value to an industry residue.